2007
DOI: 10.4103/0970-4388.37012
|View full text |Cite
|
Sign up to set email alerts
|

Retention and penetration of a conventional resin-based sealant and a photochromatic flowable composite resin placed on occlusal pits and fissures

Abstract: This study compares the retention and penetration of a conventional resin-based sealant (Fluroshield) and a photochromatic flowable composite resin (Tetric Flow Chroma) placed on occlusal pits and fissures and submitted to thermal or chemical cycling regimens. Penetration assessment--ten premolars were sealed with each material, isolated (except for the sealed surface) and immersed in 0.2% Rhodamine B. The teeth were serially sectioned in a mesiodistal direction. The images of the sections were digitized and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Dukic et al [ 28 ] noted that amongst his experimental groups, there was not a single case of caries incidence in the teeth sealed with the flowable composite, deducing that flowable composite resins when used in combination with dentin bonding agents, showed enhanced strength of the adhesive bonding to enamel in fissures by the formation of resin-tags and thus better retention rates. Additionally, an in-vitro study by Aguilar et al [ 13 ] has reported superior performance of flowable composites than conventional PFS with no statistically significant difference concerningtheir depth of penetration and retention rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dukic et al [ 28 ] noted that amongst his experimental groups, there was not a single case of caries incidence in the teeth sealed with the flowable composite, deducing that flowable composite resins when used in combination with dentin bonding agents, showed enhanced strength of the adhesive bonding to enamel in fissures by the formation of resin-tags and thus better retention rates. Additionally, an in-vitro study by Aguilar et al [ 13 ] has reported superior performance of flowable composites than conventional PFS with no statistically significant difference concerningtheir depth of penetration and retention rates.…”
Section: Discussionmentioning
confidence: 99%
“…The salivary pH ranges from neutral to acidic, and alterations in the mechanical properties of restorative materials can occur at lower pH levels. Various other factors also impede sealant retention including polymerization stress, thermocycling, water sorption, and deflection by occlusal forces, and the literature indicates that about 5–10% of sealant volume is lost per year [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have assessed the effect of plasma arc on composite resins, compomers or resin-modified glass-ionomers. 2 , 13 There are few studies conducted on the effect of this method on sealants. 4 …”
Section: Discussionmentioning
confidence: 99%
“…1 Sealant placement is considered an effective treatment modality for prevention of caries in occlusal pits and fissures. 2 Nevertheless, the preventive benefits of this treatment relies directly upon the ability of the resin sealant to thoroughly fill pits and fissures and/or morphological surface defects and remain completely intact and bonded to enamel for a life time. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%